ANALYSIS OF REALIZATION OF PRODUCTION OF ALCOHOL PRODUCTS IN OUR COUNTRY (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This thesis examines important issues related to the improvement of excise tax administration. Excise tax plays an important role in the formation of state revenues and regulation of the consumption of certain goods and services. Analyzes issues and proposes potential solutions to enhance excise tax collection, simplify administrative processes and ensure compliance. By addressing these issues, countries can optimize excise revenue and achieve better fiscal and regulatory outcomes.